PENGARUH KOMPENSASI DAN KOMPETENSI TERHADAP KINERJA GURUDI SD MUHAMMADIYAH KUTOARJO (Prospect : Jurnal Manajemen dan Akuntansi, 2021)
The aim of this research is to analyze the influence of compensation and competency on teacher performance at SD Muhammadiyah Kutoarjo. The population of this research is Permanent Foundation Teachers (GTY) who work at SD Muhammadiyah Kutoarjo. The sample used with a saturated sampling technique was 26 people. This research uses data analysis methods, namely: Likert scale, validity test, reliability test, simple linear regression analysis, coefficient of determination, t test and f test. Based on the research carried out, the results of the regression equation Y = 2.612 + 0.599 (X1) + 0.486 (X2). This means that if the value of the compensation and competency variables in the research object is equal to zero, then the level or magnitude of the teacher performance variable is 2.612. The results of the analysis of the coefficient of determination explain that 63% of compensation and competency variables contribute to teacher performance. Meanwhile, the remaining 37% is influenced by other variables that were not researched, such as ability, motivation, leadership, organizational relationships, and so on. The results of the partial hypothesis test (t test) explain that the compensation variable has a positive and significant effect on teacher performance, while the competency variable does not have a positive and significant effect on teacher performance. The results of simultaneous hypothesis testing (f test) produce a positive and significant influence between compensation variables and competency variables on teacher performance.